“How to Recognize if Your Child Is Seriously Ill” During COVID-19 Lockdown: An Evaluation of Parents' Confidence and Health-Seeking Behaviors - Lim, Emma; Mistry, Ravi D.; Battersby, Alexandra; Dockerty, Kerry; Koshy, Aaron; Chopra, Michelle N.; Carey, Matthew C.; Latour, Jos M. (Frontiers in Pediatrics, 2020)
Background: Parents’ health-seeking behaviors has changed during the COVID-19 pandemic. Providing parents’ guidance in decision-making might improve their confidence to seek timely advice when a child becomes ill. The aim of this study was to evaluate the ‘How to recognize if your child is seriously ill’ leaflet on parents’ confidence, health-seeking behaviors, and usefulness during the COVID-19 lockdown. Method: A 9-item survey, co-designed with parent advisors, was used measuring confidence and health-seeking behavior. Social media was used for data collection in a 6-week period (April–June 2020) during COVID-19 lockdown in the UK. Categorical data were analyzed as frequencies and inductive content analysis was performed with the qualitative data. Results: Totally, 171 parents responded. Most parents (n=160, 93.6%) found the leaflet helpful. The leaflet increased the confidence among 116 parents (67.8%) to recognize if their child is ill and 156 (91.2%) parents had a better understanding of when and where to seek help. Thirty-three (19.2%) parents used the leaflet while their child was unwell during COVID-19 lockdown and in 14 (42%) cases, the leaflet resulted in changing health-seeking behavior for that episode. Twelve of these parents decided to seek medical consultation when they had not planned to before. Content analysis revealed three categories; 1) Knowledge, parents found the leaflet an objective source to validate their concerns; 2) Usability, parents reported the leaflet was clearly designed; 3) Decision-aid, parents commented the leaflet provided clarification around recognition of serious symptoms and when and where to seek appropriate care. Conclusions: Our leaflet provided parents guidance on decision-making and risk-assessment of ill children during COVID-19 lockdown. Parents found it helpful; it increased their confidence and positively changed their health-seeking behaviors. Providing parents with targeted information to recognize serious illness in children at home could potentially foster self-care and safely maintain a reduction of pediatric emergency attendances for self-limiting illnesses.